2023
DOI: 10.3389/fmars.2022.1082975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and function of two tumor necrosis factor receptor-associated factors genes (TRAF2 and TRAF4) from Pinctada fucata martensii

Abstract: Tumor necrosis factor receptor-associated factors (TRAFs) have been studied in a few mollusks and participate in various biological processes, like apoptosis, immune response, stress, and inflammatory response. However, TRAFs’ function and mechanism of pearl oysters (Pinctada fucata martensii) are still unclear. In this study, we identified novel PmTRAF2 and PmTRAF4 from P. f. martensii. The deduced PmTRAF2 and PmTRAF4 proteins contain TRAF-type zinc finger domain and MATH domain, while PmTRAF4 lacks a RING fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…TRAF2 is involved in the signaling pathways of tumor necrosis factor receptors (TNFRs), which can induce either cell survival or apoptotic cell death. Studies have shown that TRAF2 can interact with other proteins, such as TRAF6, which can affect the downstream immune signaling in the various cellular processes [ 25 ]. The dynamics of TRAF2 are influenced by the length of its tail, with longer tails affecting the dynamics of the globular regions in the protein's C-terminal head [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRAF2 is involved in the signaling pathways of tumor necrosis factor receptors (TNFRs), which can induce either cell survival or apoptotic cell death. Studies have shown that TRAF2 can interact with other proteins, such as TRAF6, which can affect the downstream immune signaling in the various cellular processes [ 25 ]. The dynamics of TRAF2 are influenced by the length of its tail, with longer tails affecting the dynamics of the globular regions in the protein's C-terminal head [ 26 ].…”
Section: Discussionmentioning
confidence: 99%